Study of Raw Materials for Making Ceramic Product and Physico-Mechanical Properties of Ceramic Product Made from Rock Residue Powder - Vijayaragavan1, R.; Mullainathan3, S. (Asian Journal of Chemistry, 2013)
The present research work is on the use of the rock waste material (rock residue powder) for manufacturing ceramic product. The mineral phases and chemical composition of raw materials (fire clay and rock residue) were determined by X-ray diffraction and standard chemical analysis method respectively. In the present investigation, the mixture of various proportions of rock residue and fire clay material are used to make ceramic body specimens and these specimens fired at 800 ºC. The (unfired and fired) ceramic bodies were investigated to determine their physical and mechanical properties. All the results were indicated that the physico-mechanical behaviour increases with increasing rock waste content.